Wavelet Transforms Based Power Transformer Protection from Magnetic Inrush Current - P. Soundiraraju; N. Loganathan (Institute of Advanced Engineering and Science, 2015)
The Power transformer is the very essential element in the power systems. For wealthy running operation of power transmission and distribution, the transformer set-up is indispensable. Otherwise, under fault situation the whole transmission system will lead to power loss. The protection is necessary for power transformers i.e. mostly against internal faults and magnetic inrush currents. Exciting magnetic inrush current will tide, when the transformer is operated without keeping load or in the Voltage recovery after the fault being separated. This work suggests to develop transient detection techniques using wavelet transform for all these faults. The wavelet transform has a benefit of representation of current and Voltage signals. Empathy of transients is very fast and precise the research proposes to expand a new wavelet method to identify inrush currents to classify it from power system disturbances. The suggested practice extract faults and inrush generated transient signals using wavelet transform process. DOI: http://dx.doi.org/10.11591/telkomnika.v14i3.7849